Skin grafts and substitutes developed by Tissue Engineering - Chaves-Rodríguez, María Inés (2015)
Tissue Engineering strategies for tissue and organ regeneration have allowed the fabrication and commercialization of diverse skin substitutes, which have been applied in different parts of the world on human patients over the course of the last 30 years. These grafts have been developed using biodegradable materials (of natural or synthetic origin) as scaffolds for the adhesion and proliferation of cells that may be of different origins (autologous, allogenic and xenogenic). The main clinical advantage of these materials is to provide an effective re-epitelization of large wounds, which is particularly relevant when there is little tissue available for autografts. Also, skin equivalents provide coverage for skin lesions, avoiding dehydration and microbial infections. Despite these advantages, there are still many challenges to solve including the immediate functionality and long term permanency of the grafts and the exact reproduction of the normal tissue structure and physiology. In Costa Rica, the only laboratory dedicated to in vitro skin cell culture for reconstructing epithelial equivalents with therapeutic applications is located at the Biotechnology Research Center at the Costa Rica Institute of Technology.